The Relationship Between Sport Locus of Control and Perceived Stress Levels in Young Student-Athletes - Muhammad Kashif; Dr. Abida Naseer; Madiha Batool; Sana Akbar; Asad Ali; Asim Akbar* (Dialogue Social Science Review (DSSR), 2025)
The purpose of this study was to examine the relationship between sport locus of control and perceived stress levels among young student-athletes. A total of 200 student-athletes (M age_ = 20.34 years, SD = 1.87) from various sports disciplines participated in the study. The Sport Locus of Control Scale (SLCS) and the Perceived Stress Scale (PSS-10) were administered to assess internal versus external control orientations and perceived stress levels, respectively. Descriptive statistics indicated a moderate tendency toward an internal sport locus of control (M = 3.62, SD = 0.74) and moderate perceived stress levels (M = 18.45, SD = 5.32). Pearson’s correlation analysis revealed a significant negative relationship between sport locus of control and perceived stress (r = –.46, p < .001), indicating that athletes with a stronger internal locus of control reported lower stress. Independent-samples t-tests showed no significant differences in perceived stress levels by gender (p > .05). Multiple regression analysis indicated that sport locus of control was a significant predictor of perceived stress (β = –.43, p < .001), explaining 21% of the variance. These findings suggest that interventions designed to foster a more internal locus of control orientation may help reduce stress among young athletes, potentially enhancing both psychological well-being and performance. The study contributes to the growing literature on psychological determinants of stress in sports contexts and offers practical implications for coaches, sport psychologists, and athletic programs. Keywords: Sport Locus Of Control, Perceived Stress, Student-Athletes, Regression Analysis, Psychological Well-Being